Heavy metal concentrations in soils and vegetation in urban areas of Quezon City, Philippines - Navarrete, Ian A (Archīum Ateneo, 2017)
Limited data have been published on the chemistry of urban soils and vegetation in the Philippines. The aim of this study is to quantify the concentrations of heavy metals (i.e., Cr, Ni, Cu, Zn, and Pb) in soils and vegetation in the urban landscape of Quezon City, Philippines, and to elucidate the relationships between soil properties and the concentration of heavy metals pertaining to different land uses [i.e., protected forest (LM), park and wildlife area (PA), landfill (PL), urban poor residential and industrial areas (RA), and commercial areas (CA)]. Soil (0–15 cm) and senescent plant leaves were collected and were analyzed for soil properties and heavy metal concentrations. Results revealed that the concentrations of heavy metals (i.e., Cr, Ni, Cu, Zn, and Pb) in urban soils were higher in areas where anthropogenic activities or disturbance (PL, RA, and CA) were dominant as compared to the less disturbed areas (LM and PA). Organic matter and available phosphorous were strongly correlated with heavy metal concentrations, suggesting that heavy metal concentrations were primarily controlled by these soil properties. The average foliar heavy metal concentrations varied, ranging from 0 to 0.4 mg/kg for Cd, 0–10 mg/kg for Cr, 2–22 mg/kg for Cu, 0–5 mg/kg for Pb, and 11–250 mg/kg for Zn. The concentrations of Cd and Cr exceeded the critical threshold concentrations in some plants. Leaves of plants growing in PL (i.e., landfill) showed the highest levels of heavy metal contamination. Our results revealed that anthropogenic activities and disturbance caused by the rapid urbanization of the city are major contributors to the heavy metal accumulation and persistence in the soils in these areas.